PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH DALAM PENINGKATAN PEMBELAJARAN IPS TENTANG KEGIATAN EKONOMI DALAM MEMANFAATKAN SUMBER DAYA ALAM PADA SISWA KELAS IV SDN 1 KALIJIREK TAHUN AJARAN 2014/2015 - Sucahyo, Aji (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Make A Match Cooperative Model in Improving Social Studies Learning about Economic Activities in Utilizing Natural Resources for The Fourth Grade Students of SDN 1 Kalijirek in Academic Year of 2014/2015.The aims of this research are: to describe and improving the application of make a match cooperative model of social studies learning about economic activities in utilizing natural resources, and to find out problems and solutions in the implementation of make a match cooperative model. This research is Classroom Action Research (CAR) conducted within three cycles, each cycle consisted of two meetings and each meeting consisted of four steps: planning, action, observation, and reflection. Subjects in this research are all fourth grade students at SDN 1 Kalijirek in academic year of 2014/2015 totalling 24 students. The conclusions of this study are social studies learning about economic activities in utilizing natural resources through the implementation of make a match cooperative model has improved significantly, percentage of students completeness reached 87.50%. Keywords: cooperative model, make a match, social studies learning Abstrak: Penerapan Model Kooperatif Tipe Make A Match dalam Peningkatkan Pembelajaran IPS tentang Kegiatan Ekonomi dalam Memanfaatkan Sumber Daya Alam pada Siswa Kelas IV SDN 1 Kalijirek Tahun Ajaran 2014/2015. Tujuan penelitian ini untuk mendiskripsikan dan meningkatkan penerapan model kooperatif tipe make a match, menemukan kendala dan solusi penerapan model kooperatif tipe make a match. Penelitian ini adalah penelitian tindakan kelas dengan menggunakan tiga siklus, setiap siklus dua pertemuan dan setiap pertemuan terdiri dari empat tahapan yaitu perencanaan, tindakan, observasi, dan refleksi. Subjek pada penelitian ini adalah seluruh siswa kelas IV SDN 1 Kalijirek Tahun Ajaran 2014/2015 yang berjumlah 24 siswa. Kesimpulan penelitian ini adalah penerapan model kooperatif tipe make a match dapat meningkatkan pembelajaran IPS pada siswa kelas IV SDN 1 Kalijirek, persentase ketuntasan siswa mencapai 87,50%. Kata Kunci: model kooperatif, make a match, IPS